2018
DOI: 10.2147/jpr.s152349
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study: serum CCL3/MIP-1α levels may reflect lumbar intervertebral disk degeneration in Han Chinese people

Abstract: BackgroundThe macrophage inflammatory protein-1α (MIP-1α), also named chemokine cytokine ligand 3 (CCL3), has been detected in nucleus pulposus and increased following cytokine stimulation.ObjectiveThe current study was performed to explore the relationship between serum CCL3/MIP-1α levels with lumbar intervertebral disk degeneration (IDD).Patients and methodsA total of 132 disk degeneration patients confirmed by magnetic resonance imaging and 126 healthy controls were enrolled in the current study. Radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It may be relevant to briefly relate the five most important saliva proteins (MIP-1α/CCL3, I-TAC/CXCL11, MCP-4/CCL13, MIP-3β/CCL19 and IL-2) to studies concerning nociception and pain. The chemokine MIP - 1α/CCL3 has inflammatory properties ( 79 ), and elevated blood levels have been reported in chronic widespread pain (mainly FM), lumbar intervertebral disk degeneration, migraine, and prostatitis pelvic pain ( 75 , 80 82 ). I - TAC/CXCL11 is a proinflammatory chemokine and increased blood levels have been found in FM and in endometriosis patients ( 79 , 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may be relevant to briefly relate the five most important saliva proteins (MIP-1α/CCL3, I-TAC/CXCL11, MCP-4/CCL13, MIP-3β/CCL19 and IL-2) to studies concerning nociception and pain. The chemokine MIP - 1α/CCL3 has inflammatory properties ( 79 ), and elevated blood levels have been reported in chronic widespread pain (mainly FM), lumbar intervertebral disk degeneration, migraine, and prostatitis pelvic pain ( 75 , 80 82 ). I - TAC/CXCL11 is a proinflammatory chemokine and increased blood levels have been found in FM and in endometriosis patients ( 79 , 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, future mechanistic studies with IL-1 receptor-blocking antibodies will enable us to better understand how IL-1β induction by C. acnes from disc cells could modulate other inflammatory mediators. Previous investigations have shown that expression levels of IL-6, IL-8, CCL3 and CCL4 increase in degenerate IVDs where they appear to play pivotal roles in disc tissue remodelling and nerve sensitisation [ 55 , 56 , 57 ]; furthermore, serum levels of IL-6, IL-8 and CCL3 are elevated in patients with disc degeneration, and the release of a cytokine cocktail from disc cells can also activate a pro-inflammatory response from bone marrow cells, which could potentially lead to the development of Modic changes [ 45 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCL2, CCL5, CXCL6, CXCL12, CXCL20, C-X-C receptor 4 (CXCR4), and stromal cell-derived factor 1 (SDF1) expression is considerably elevated in IDD tissues [159][160][161][162][163]. Serum CCL3, CXCL12, and SDF1 levels have also been demonstrated to be positively associated with the degree of IDD [137,162,164,165]. Chemokines may have a role in IDD through a variety of pathways.…”
Section: Chemokinesmentioning
confidence: 99%